REPRESENTASI CITRA MUSLIMAH DALAM IKLAN WARDAH COSMETICS “BERGERAK HIDUPKAN HARAPAN” EDISI RAMADHAN 1443 H - Amaniah, Suci; Afyatul Masruroh, Sayyidah (Universitas Hasyim Asy'ari, 2024)
Advertising is a promotional medium used by various companies to increase sales of services and goods. Television commercials are believed to be able to influence audiences to purchase products. Moreover, using female figures can increase the appeal of an ad because of their beauty. Many commercials feature female figures showing their curves, such as those featuring women in short, tight clothing. However, unlike Wardah Cosmetics' commercial